Atributos químicos e físicos do solo da planície hipersalina do estuário do rio Apodi - Mossoró - Costa, Lucas Ramos da (2018)
Due to its important role and position of transition between sea and land, estuarine environments have been the object of study of several areas of science. However, few studies have focused on the understanding of chemical and physical relationships, as well as the spatial and chemical variation of estuarine soils. However, with the occupation and exploration of the land for diverse uses, the variability is accentuated. Nowadays, work on spatial variation of soil attributes helps in decision making and application of effective solutions to the detriment of environmental risks. The objective of this work was to understand the existing relationships of chemical and physical attributes in three areas of the hypersaline plain of the Apodi-Mossoró estuary. To reach the objective, 52 samples, with a volume of 1 kg, were collected at the depths of 0.5, 1.0, 2.0 and 3.0m e in three areas called S, C and N, and each point of georeferenced collection was used, if a GPS navigation. Multivariate analysis is an efficient tool in discriminating the three areas studied. The levels of heavy metals in the estuary are within the limits established by Brazilian legislation. The Apodi- Mossoró River estuary is characterized as fluvial sediments such as sands of different granulometries, followed by transition sedimentation, silt contributes to the formation of the estuary floor. The Apodi-Mossoró River estuary is classified as apicum area, because the sodium concentrations are in intervals of 100 and 130 cmolc dm-3. The area S has the highest concentrations of sodium and the excess of salts in the soil contributes to the higher degree of flocculation